Periplasmic Peptidyl Prolyl cis-trans Isomerases Are Not Essential for Viability, but SurA Is Required for Pilus Biogenesis in Escherichia coli - Justice, Sheryl S. (American Society for Microbiology, 2005)
In Escherichia coli, FkpA, PpiA, PpiD, and SurA are the four known periplasmic cis-trans prolyl isomerases. These isomerases facilitate proper protein folding by increasing the rate of transition of proline residues between the cis and trans states. Genetic inactivation of all four periplasmic isomerases resulted in a viable strain that exhibited a decreased growth rate and increased susceptibility to certain antibiotics. Levels of the outer membrane proteins LamB and OmpA in the quadruple mutant were indistinguishable from those in the surA single mutant. In addition, expression of P and type 1 pili (adhesive organelles produced by uropathogenic strains of E. coli and assembled by the chaperone/usher pathway) were severely diminished in the absence of the four periplasmic isomerases. Maturation of the usher was significantly impaired in the outer membranes of strains devoid of all four periplasmic isomerases, resulting in a defect in pilus assembly. Moreover, this defect in pilus assembly and usher stability could be attributed to the absence of SurA. The data presented here suggest that the four periplasmic isomerases are not essential for growth under laboratory conditions but may have significant roles in survival in environmental and pathogenic niches, as indicated by the effect on pilus production.